Effects of shape, size and solid content of Al pigments on the low-infrared emissivity coating. (April 2015) - Yuan, L.; Weng, X. L.; Xie, J. L.; Deng, L. J.
<x content-type="archive" xml:space="preserve">Abstract</x> Low infrared emissivity coating was prepared by the aluminium (Al) pigments and epoxy resin. The effect of shape, size and solid content of Al pigments on infrared emissivity was systematically investigated. The results indicated that the optimised Al particles with the minimum infrared emissivity are micrometer-scale flaky, high-solid content and large particle size. Anisotropic flaky pigment is easy to form directional distribution in the direction of coating surface, which could increase the available reflection area. High concentration of flaky Al pigment helps to form a high-infrared reflectance layer on the coating's surface because they are directional arranged very closely to each other. It effectively reduces the infrared absorption of epoxy resin. Additionally, the influence mechanism of pigment size on the infrared emissivity is explained by the rough surface theory, which indicates that the low-surface roughness can be obtained for the coating with big size pigments, which plays an important role in the formation of low emissivity coating.